2010
DOI: 10.2353/ajpath.2010.091129
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Induces Epidermal Growth Factor Receptor-Dependent Redistribution of Apical MUC1 and Junctional β-Catenin in Polarized Human Airway Epithelial Cells

Abstract: Cigarette smoke (CS) accounts for nearly 90% of lung cancer deaths worldwide; however, an incomplete understanding of how CS initiates preneoplastic changes in the normal airway hinders early diagnosis. Short-term exposure to CS causes aberrant activation of epidermal growth factor receptor (EGFR) and canonical Wnt/␤-catenin signaling pathways in human bronchial epithelial (HBE) cells. We hypothesize that this response is elicited through the disruption of spatially segregated cell membrane proteins in the pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 41 publications
(48 reference statements)
2
42
0
Order By: Relevance
“…Similarly, previous findings showed that the MUC1-CT-ERa transcription complex protected and stabilized ERa by attenuating its ubiquitination and degradation, 16 and a protective role of b-catenin degradation by the b-catenin-MUC1-CT transcription complex was similarly proposed. 17 These findings are in line with a possible protective role of MUC1-CT on GRa.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similarly, previous findings showed that the MUC1-CT-ERa transcription complex protected and stabilized ERa by attenuating its ubiquitination and degradation, 16 and a protective role of b-catenin degradation by the b-catenin-MUC1-CT transcription complex was similarly proposed. 17 These findings are in line with a possible protective role of MUC1-CT on GRa.…”
Section: Discussionsupporting
confidence: 80%
“…16 Similar findings were observed for the b-catenin-MUC1-CT transcription complex as a modulator of morphogenesis. 17,18 Corticosteroids exert their anti-inflammatory functions by binding to their intracellular receptor, the glucocorticoid receptor (GR), which is a ligand-inducible transcription factor. In the absence of its ligand, GR resides predominantly in the cytoplasm, where it is sequestered in a multimeric chaperone complex comprising heat-shock protein (hsp) 90, hsp70, hsp90-binding protein p23, immunophilins, and other factors to prevent its degradation and assist in its maturation.…”
mentioning
confidence: 99%
“…Activation of EGFR results in increased production of MUC5AC in the airway epithelium (196), and P. aeruginosa induces MUC5AC via activation of MAPK and EGFR (57,197,198). Increased mucin is a response to tobacco smoke (197), and EGFR serves as a gateway for cigarette smoke to mediate its damaging effects on adherens junctions and Wnt/ b-catenin signaling (199). TACE is an integral component of this response because inhibiting TACE prevents the increased mucin expression as a result of reduce TGF-a shedding (198) An interplay exists between EGFR signaling and the TLRs.…”
Section: Egfrmentioning
confidence: 99%
“…Consistent with this notion, cigarette smoke in combination with IL-1 has been shown to induce disassembly of tight junction complex in endothelial cells by suppressing PTEN activity (Barbieri et al, 2008). Chen et al showed that cigarette smoke also alters epithelial permeability by disrupting cell polarity via activation of EGFR, dissociation of -catenin and E-cadherin from adherence junctional complex and redistribution of apical MUC1 membrane bound mucin to cytoplasm (Chen et al, 2010). In a homestatic epithelium, -catenin cooperates with E-cadherin to form apical junctional complex and maintain cell polarity (Xu and Kimelman, 2007).…”
Section: Junctional Adherens Complexes and Airway Epithelial Permeabimentioning
confidence: 55%
“…In airway regeneration or oncogenic formation -catenin translocates to nucleus, and activates canonical Wnt signaling pathway (Mazieres et al, 2005;Tian et al, 2009). Similar to -catenin, the cytoplasmic tail of MUC1 also supports structural barrier during homeostasis (Chen et al, 2010). Since cigarette smoke causes aberrant activation of both EGFR and canonical Wnt/ -catenin signaling (Khan et al, 2008;Lemjabbar et al, 2003), it is plausible that chronic cigarette smoke exposure decreases barrier function and promote microbial invasion of airway epithelium.…”
Section: Junctional Adherens Complexes and Airway Epithelial Permeabimentioning
confidence: 99%